Epidemiologia molecular de infecções hospitalares da corrente sanguínea por Staphylococcus aureus resistentes à oxacilina: Estudo multicêntrico (Projeto SCOPE Brasil) - Paschoal, Loren [UNIFESP] (2010)
General objective: Phenotypic and genotypic characterization of methicillin-resistant S. aureus (MRSA) collected from bloodcultures from several centers participants of Brazilian SCOPE Project, from June 2007 to July 2009. Specific Objectives: (i) to assess the different types of SCCmec distribution through conventional and multiplex PCR for the different participant institutions; (ii) to detect the possible presence of lukF gene, which codes for PVL toxin (Panton Valentine Leukocidin); (iii) to assess the genetic similarity of these samples through PFGE and MLST and (iv) to determine the oxacillin and vancomycin minimal inhibitory concentration (MIC). Material and Methods: Sixty two MRSA isolated from the first episode of bloodstream infection (BSI) were evaluated. These samples came from patients hospitalized at the 11 medical centers from different regions of the country. The oxacillin-resistant isolated were submitted to conventional PCR to detect nuc and lukF genes and to multiplex PCR to identify SCCmec types. Agar dilution and E-test for vancomycin were performed. The strains were molecular typed by PFGE and MLST. Results: From the total of 62 samples, 29 amplified SCCmec type III, 16 SCCmec type II, 9 SCCmec type IV, 6 SCCmec type I and 2 could not be identified. A sample with SCCmec subtype IVc carried the gene which codifies for PVL. Samples with SCCmec types I, II and III showed MIC > 256 ƒÊg/ml for oxalicin by EtestR. Just one of them, with SCCmec type II, presented MIC = 128 ƒÊg/ml. From the nine samples with SCCmec type IV, six presented MIC . 48 ƒÊg/ml. MICs of 1.0, 1.5 e 2.0 ƒÊg/ml were also observed for vancomycin by EtestR. Regarding the agar dilution, two samples presented MICs of 2.0 ƒÊg/ml and all the others showed values between 0.5 e 1.0 ƒÊg/ml. From the 8 MRSA samples typed by MLST, it was observed ST105 in a sample with SCCmec type I; ST5 and ST105 in samples with SCCmec type II, ST239 with SCCmec type III and ST5 and ST1176 with SCCmec type IV. Conclusion: The majority of samples were MRSA carrying SCCmec type III and genetically related to CEB clone. Also were detected samples SCCmec type II and IV, related to New York/Japan and Pediatric clones in different hospitals at different regions of the country. Only one sample SCCmec type IV (subtype IVc) not related to any clone was positive for PVL. Only two common genetic ancestral (CC5 and CC8) were observed through MLST and a new ST1176 was characterized. No vancomycin-resistant isolate was detected.